Effect of irradiation on volatile compound profiles and lipid oxidation in chicken powder seasoning. (February 2022) - Zheng, Qi; Wang, Haihong; Yue, Ling; Yan, Weiqiang; Guo, Hongxia; Chen, Zhijun; Qi, Wenyuan; Kong, Qiulian
Abstract: The effects of two types of industrial irradiation sources (10 MeV electron beam (EB) and gamma ray (GR), irradiation at 4 kGy and 7 kGy, respectively) on off-odor, volatile compounds, and lipid oxidation in chicken powder seasoning were studied. Irradiation induced off-odor and lipid oxidation in a dose-dependent manner. EB was better than GR at the same dose, with less off-odor and lower peroxide value (POV) and thiobarbitunic acid reactive substance (TBARS) values. GC/MS analysis revealed the presence of 121 volatile compounds, including 113 in non-irradiated chicken powder seasoning followed by 98 in EB 4 kGy, 91 in EB 7 kGy, 80 in GR 4 kGy, and 76 in GR 7 kGy. Irradiation decreased terpenes and terpenoids, and increased aldehydes/alkenes and induced formation of E−1, 8-dodecadiene, which correlated to increasing radiation dose. EB induced higher alkenes, terpenes, and terpenoids as well as lower aldehydes than GR at the same dose. In GR 7 kGy-irradiated chicken powder seasoning, 3-octen-2-one, 3, 5-octadien-2-one, hexanal, and hexanoic acid were higher than other irradiation treatments. These results suggest that dose contributes to off-odor intensity, and EB has an advantage over GR for chicken powder seasoning irradiation, with more original volatile compounds, lower off-odor, and less lipid oxidation. Highlights: Effect of e-beam and γ-ray irradiation on chicken powder seasoning odor was studied. Irradiation induced off-odor and lipid oxidation in a dose-dependent manner. Irradiation led to terpenes and terpenoids decrease, alkenes and aldehydes increase. E-beam is better to reduce chicken powder seasoning odor than γ-ray at same dose.